ANALISIS YURIDIS KEDUDUKAN MAHAR DALAM HUKUM PERKAWINAN - Dwi Apriliyani J Nusi,; Nur Mohamad Kasim,; Weny Almarovid Dungga, (The Juris, 2023)
This article aims to find out how Mahar's position on the law of marriage in particular for Islamic believers where the obligation of Mahar is a thing to be carried out and how the compilation of Islamic law views on the Mahar arrangement. But the reality is that there is still a divergence in the society that from the prospect of the bride to the prospective bride asks Mahar to a very oppressive male prosecutor so that the prosecuted bride is unable to hold it that eventually the candidate bride and bride take the crossroads of fleeing to the place of the Principal. So to reveal that, the author uses the Library Research approach with the research methods carried out to study literature and writings that are closely related to the issues raised in this research. The functions of the Mahar are: a. the distinction between marriage and marriage; b. the form of respect, appreciation, and protection for women; c. the type of seriousness of a man toward the woman he is to marry; d. the symbol of the responsibility of a woman toward a given Mahar; e. a symbol of responsibility for a man; and f. the symbole of agreement and disagreement.